Correlations of life form, pollination mode and sexual system in aquatic angiosperms. - Zhi-Yuan Du; Qing-Feng Wang (PLoS ONE, 2014)
Aquatic plants are phylogenetically well dispersed across the angiosperms. Reproductive and other life-history traits of aquatic angiosperms are closely associated with specific growth forms. Hydrophilous pollination exhibits notable examples of convergent evolution in angiosperm reproductive structures, and hydrophiles exhibit great diversity in sexual system. In this study, we reconstructed ancestral characters of aquatic lineages based on the phylogeny of aquatic angiosperms. Our aim is to find the correlations of life form, pollination mode and sexual system in aquatic angiosperms. Hydrophily is the adaptive evolution of completely submersed angiosperms to aquatic habitats. Hydroautogamy and maleflower-ephydrophily are the transitional stages from anemophily and entomophily to hydrophily. True hydrophily occurs in 18 submersed angiosperm genera, which is associated with an unusually high incidence of unisexual flowers. All marine angiosperms are submersed, hydrophilous species. This study would help us understand the evolution of hydrophilous pollination and its correlations with life form and sexual system.